ANALISIS KEMAMPUAN INOVASI PEMBELAJARAN GURU SEKOLAH DASAR DALAM IMPLEMENTASI PEMBELAJARAN TEMATIK KURIKULUM 2013 DI SEKOLAH DASAR - Anna Mariyani (Universitas Muhammadiyah Surakarta, 2019)
The thematic approach must be implemented at all levels of education in the learning process for elementary school, junior high school and senior high school. This is something that is important for teachers, one of which is elementary school teachers to be able to carry out a thematic approach as a professional responsibility. In addition to implementing a thematic approach, elementary school teachers must also always innovate in implementing the education process. This study was conducted with the following objectives: 1) analyzing elementary school teachers 'understanding of the thematic approach, 2) obtaining a profile of elementary school teachers' ability to innovate in the learning process with a thematic approach, and 3) knowing the obstacles of teachers in implementing thematic approaches in elementary school. The study used a qualitative descriptive method with research subjects from grade 1 to grade 6 students in five elementary schools in Blora District, Blora Regency, collected by observation and interview. Triangulation is done through focus group discussions between researchers, teachers, and school principals. The results showed that conceptually the teacher understood the thematic approach well, but in its implementation 24 of the 30 teachers studied did not innovate in the learning process